Asthma and COPD "Overlap": a Treatable Trait or Common Several Treatable-Traits? - Gaspar Marques, J (2020)
In the last years, disease classification of chronic respiratory diseases (CRD) has been vivaciously discussed and new concepts have been introduced, namely asthma-chronic obstructive pulmonary disease (COPD) overlap (ACO). Controversially the GOLD consensus document of 2020 considered that we should no longer refer to ACO, as they constitute two different diseases that may share some common traits and clinical features. The treatable traits approach has numerous strengths that are applicable to several levels of health care. In this paper we review the application of the treatable traits to CRD and describe in detail the ones already identified in patients with asthma and COPD. Treatable traits in CRD can be divided in pulmonary, extra-pulmonary and behavior/lifestyle risk factors. Patients with both asthma and COPD patients have clearly recognized treatable traits in all these subtopics but it is notorious the severe and frequent exacerbations, the associated cardiovascular disease and the low health related quality of life and productivity of these patients.